Ultramicronized Palmitoylethanolamide (um-PEA): A New Possible Adjuvant Treatment in COVID-19 patients - Annalisa Noce; Maria Albanese; Giulia Marrone; Manuela Di Lauro; Anna Pietroboni Zaitseva; Daniela Palazzetti; Cristina Guerriero; Agostino Paolino; Giuseppa Pizzenti; Francesca Di Daniele; Annalisa Romani; Cartesio D'Agostini; et al. (MDPI AG, 2021)
The Coronavirus Disease-19 (COVID-19) pandemic has caused more than 100,000,000 cases of coronavirus infection in the world in just a year, of which there were 2 million deaths. Its clinical picture is characterized by pulmonary involvement that culminates, in the most severe cases, in acute respiratory distress syndrome (ARDS). However, COVID-19 affects other organs and systems, including cardiovascular, urinary, gastrointestinal, and nervous systems. Currently, unique-drug therapy is not supported by international guidelines. In this context, it is important to resort to adjuvant therapies in combination with traditional pharmacological treatments. Among natural bioactive compounds, palmitoylethanolamide (PEA) seems to have potentially beneficial effects. In fact, the Food and Drug Administration (FDA) authorized an ongoing clinical trial with ultramicronized (um)-PEA as an add-on therapy in the treatment of Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) infection. In support of this hypothesis, in vitro and in vivo studies have highlighted the immunomodulatory, anti-inflammatory, neuroprotective and pain-relieving effects of PEA, especially in its um form. The purpose of this review is to highlight the potential use of um-PEA as an adjuvant treatment in SARS-CoV-2 infection.